Correlación entre el test de campo en tierra de 1000 metros para resistencia aeróbica y un test adaptado en agua de 300 metros en estilo libre para niños de 9 a 10 años del CIFAR de la Liga de Natación de Antioquia (2018)
This research project starts as an initiative of the University of San Buenaventura in conjunction with the CIFAR of the Liga De Natación De Antioquia (to determine the degree of correlation between the field test of 1000 meters for aerobic resistance and a test adapted in water Of 300 meters in freestyle for children of 9 to 10 years old of this center) starting from this macro investigation and once obtained the general result of such tests, to have the scientific evidence coherent according to ages and specificity of the sport to be able to realize a Training plan according to the characteristics. In the macro application of the project, a non-experimental quantitative research of descriptive cut will be carried out to find the correlation that will be obtained now of the resistance tests: In this way, a comparison between the results found after submitting to the children to the field test of Jauregui, Nieto and Ordoñez in land of 1000 meters and a test adapted in water of 300 meters in freestyle for children of 9 to 10 years.